1985
DOI: 10.1002/em.2860070104
|View full text |Cite
|
Sign up to set email alerts
|

In vitro enhancement of the mutagenicity of 4‐nitro‐o‐phenylenediamine by plant S‐9

Abstract: The direct-acting mutagen 4-nitro-o-phenylenediamine (NOP) was activated in vitro by pea or tobacco S-9 into a more potent mutagen in Salmonella typhimurium strain TA98. NOP mutagenicity was not altered by Aroclor 1254-induced rat liver S-9. The plant S-9 activation of NOP was heat-sensitive but was not NADPH-dependent, did not involve superoxide radicals, and was not inhibited by CO. A direct relationship between plant peroxidase and NOP activation was established. Several purified peroxidases including horse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Recent investigations indicated that plant metabolism efficiently convert promutagens to mutagenic products (Higashi et al 1981;Plewa 1978;Scott et al 1978;Takehisa and Kanaya 1983). Metabolic activation in vitro with S9 preparations of several plant species including Helianthus, Nicotiana, Zea, Tradescantia resulted in the activated compounds inducing mutations in microbial test systems (Gentile et al 1985). Krahan and Heidelberger (1977) suggested that variation in activating potential depended on inducerspecific qualitative and quantitative differences in metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations indicated that plant metabolism efficiently convert promutagens to mutagenic products (Higashi et al 1981;Plewa 1978;Scott et al 1978;Takehisa and Kanaya 1983). Metabolic activation in vitro with S9 preparations of several plant species including Helianthus, Nicotiana, Zea, Tradescantia resulted in the activated compounds inducing mutations in microbial test systems (Gentile et al 1985). Krahan and Heidelberger (1977) suggested that variation in activating potential depended on inducerspecific qualitative and quantitative differences in metabolism.…”
Section: Discussionmentioning
confidence: 99%